Adhesion of 3D printed material on textile substrates. Issue 1 (2nd January 2018) - Grimmelsmann, Nils; Kreuziger, Mirja; Korger, Michael; Meissner, Hubert; Ehrmann, Andrea
Abstract : Purpose: Composites combining two or more different materials with different physical and chemical properties allow for tailoring mechanical and other characteristics of the resulting multi-material system. In relation to fiber-reinforced plastic composites, combinations of textile materials with 3D printed polymers result in different mechanical properties. While the tensile strength of the multi-material system is increased compared to the pure 3D printed material, the elasticity of the polymer layer can be retained to a certain degree, as the textile material is not completely immersed in the polymer. Instead, an interface layer is built in which both materials interpenetrate to a certain degree. The purpose of this study is to investigate the adhesion between both materials at this interface. Design/methodology/approach: This paper gives an overview of the parameters affecting the interface layer. It shows that both the printing material and the textile substrate influence the adhesion between both materials due to viscosity during printing, thickness and pore sizes, respectively. While some material combinations build strong form-locking connections, others can easily be delaminated. Findings: Depending on both materials, significantly different adhesion values can be found in such 3D printed composites. Practical implications: This makes some combinations very well suitable for building composites with novel mechanical properties, while other suffer of insufficient connections. Originality/value: For the first time, the dependence of the polymer-textile adhesion force was evaluated according to the distance between both compound partners. It was shown that this value is of crucial interest and must thus be taken into account when producing printed polymer-textile composites.